Effect of Product Quality, Company Image and Price Perception on Customer Satisfaction - Ricardo Ricardo (Dinasti Publisher, 2021)
The Literature Review article on the Effect of Product Quality, Company Image and Price Perception on Customer Satisfaction is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Product Quality has an effect on Customer Satisfaction; 2) Company Image has an effect on Customer Satisfaction; and 3) Price Perception has an effect on Customer Satisfaction. Apart from these 3 exogenous variables that affect the endogenous variable of Customer Satisfaction, there are still many other factors including Price, Service Quality and Place variables.